Case report of whole genome sequencing in the XY female: identification of a novel SRY mutation and revision of a misdiagnosis of androgen insensitivity syndrome. Issue 1 (December 2016) - De Sousa, Sunita; Kassahn, Karin; McIntyre, Liam; Chong, Chan-Eng; Scott, Hamish; Torpy, David
Abstract Background The 46, XY female is characterised by a male karyotype and female phenotype arising due to any interruption in the sexual development pathwaysin utero . The cause is usually genetic and various genes are implicated. Case presentation Herein we describe a 46, XY woman who was first diagnosed with androgen insensitivity syndrome (testicular feminisation) at 18 years; however, this was later questioned due to the presence of intact Müllerian structures. The clinical phenotype suggested several susceptibility genes includingSRY, DHH, NR5A1, NR0B1, AR, AMH, andAMHR2 . To study candidate genes simultaneously, we performed whole genome sequencing. This revealed a novel and likely pathogenic missense variant (p.Arg130Pro, c.389G>C) inSRY, one of the major genes implicated in complete gonadal dysgenesis, hence securing this condition over androgen insensitivity syndrome as the cause of the patient's disorder of sexual development. Conclusion This case highlights the emerging clinical utility of whole genome sequencing as a tool in differentiating disorders of sexual development.